The Effect Of Application Learning Cycle as Learning Model in Christian Religious Education Subjects on The Honesty of The 6th Grade Students of The Gamaliel Christian Elementary School Makassar - Ricky Putra Gala (Peneliti.net, 2020)
The purpose of this research was to find out the effect of implementation of the learning model called learning cycle in Christian Religious Education subject to the behavior of honesty of 6th grade students of Gamaliel Christian Elementary School in Makassar. This learning model consists of five phases, such as the exploring phase, planning phase, implementation phase, communication phase and reflection phase. The method used in this research was quantitative with a research and development (R&D) approach. The research has been conducted by spreading questionnaires both to teachers and students themselves then analyzed the result through descriptions or exposure. In addition, the author also conducted literature studies and interviews with the competent people. The data analysis technique in this study used a rating scale. Based on the results of the research, it can be concluded that the implementation of the learning cycle as a learning model has a good effect for the behavior of honesty of the Gamaliel Christian elementary students in Makassar. It shows from the observation of student activities in a school environment such as: students being honest, dare to admit for the mistakes and not blaming the others.